2019
DOI: 10.1136/gutjnl-2019-319114
|View full text |Cite
|
Sign up to set email alerts
|

Myristoleic acid produced by enterococci reduces obesity through brown adipose tissue activation

Abstract: ObjectiveDietary fibre has beneficial effects on energy metabolism, and the majority of studies have focused on short-chain fatty acids produced by gut microbiota. Ginseng has been reported to aid in body weight management, however, its mechanism of action is not yet clear. In this study, we focused on the potential modulating effect of ginseng on gut microbiota, aiming to identify specific strains and their metabolites, especially long-chain fatty acids (LCFA), which mediate the anti-obesity effects of ginsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 43 publications
6
118
0
Order By: Relevance
“…Recent findings suggest that the metabolic activities of enteric microbiota may affect the levels of long-chain fatty acids [47]. Oral gavage of Enterococcus faecalis has been reported to affect a variety of long-chain fatty acids, including palmitoleic [48]. In addition, increased palmitoleic acid was previously observed in mice fed gut Bifidobacterium breve [49] and Lactobacillus rhamnosus LA68 [50].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that the metabolic activities of enteric microbiota may affect the levels of long-chain fatty acids [47]. Oral gavage of Enterococcus faecalis has been reported to affect a variety of long-chain fatty acids, including palmitoleic [48]. In addition, increased palmitoleic acid was previously observed in mice fed gut Bifidobacterium breve [49] and Lactobacillus rhamnosus LA68 [50].…”
Section: Discussionmentioning
confidence: 99%
“…Enterococcus was the main driver of difference between the FGF15 INT-KO Sham and VSG groups at the genus level ( Figure 6D). Increase in Enterococcus species in the gut has been linked to decreased adiposity as a result of increased energy expenditure (Quan et al, 2019). A recent study showed that a probiotic cocktail of Lactobacillus and Enterococcus prevented dietinduced inflammation and leaky gut by increasing bile acid hydrolase activity (Ahmadi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Branched chain amino acids (BCAAs), such as leucine (Leu), isoleucine (Ile), and valine (Val), work both as the substrates for anabolism of nitrogenous compounds and as signaling molecules regulating energy homeostasis via multiple signaling networks, including the phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway (Nie et al, 2018). Gut microbiota also participates in fermentation of BCAA and generates a complex mixture of metabolites, including ammonia, SCFAs, and branched-chain fatty acids (valerate, isobutyrate, and isovalerate).…”
Section: Tcm Affects Gut Microbiota That Produces Functional Amino Acmentioning
confidence: 99%
“…The changed gut microbiota composition by TCM herbs administration may contribute to the ameliorative effects on abnormal lipids metabolism (Huang et al, 2019;Zhang et al, 2019a). On the other hand, ginseng extract can enrich Enterococcus faecalis that produces an unsaturated long chain fatty acid, myristoleic acid (MA), leading to reducing adiposity by activation of brown adipose tissue (BAT) and formation of beige fat (Quan et al, 2019). Therefore, modulation of gut microbiota bacteria by TCM herbs may produce optimal amounts of beneficial lipid metabolites, which is an effective strategy for promotion of well-being in hosts.…”
Section: Tcm-affected Gut Microbiota Produces Functional Metabolites mentioning
confidence: 99%